Innovation and business performance for Spanish SMEs: New evidence from a multi-dimensional approach. - Expósito-García, Alfonso; Sanchis-Llopis, Juan Alberto (Sage, 2018)
This article examines the impact of product, process and organisational innovations on two alternative dimensions of business performance: finance and operations. Two indicators capture financial performance: sales increase and production cost reduction. Operational firm performance is captured by two alternative indicators: productive capacity augmentation and quality improvement of product/service provided by the firm. Using a wide-ranging sample of Spanish small- and medium-sized enterprises (SMEs), our findings highlight the significant impact of innovation upon both these dimensions of business performance, although they differ regarding the type of innovation and the performance indicator considered. Furthermore, our results indicate that the relationship between innovation choices in SMEs and business performance should be analysed from a multi-dimensional approach. These findings reveal significant implications for innovation policies and strategies for SMEs.
Copyright de los autores.
Keywords: Pequeñas y medianas empresas - Gestión; Creatividad en la empresa; Econometría; Business performance; Innovation; Multi-dimensional analysis; SME; Spain